2007
DOI: 10.1002/pdh.232
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of an action learning set

Abstract: This paper outlines the background to the establishment of a multidisciplinary action learning set in the Irish Health Service context; describes the action learning set process; explores set members' experiences of set membership and action learning; and concludes by making some recommendations. Copyright © 2007 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…(p. 21). Bell et al (2007) suggested that action learning promotes individual ownership of learning and development. Brook (2010), in a national survey within the NHS in 2004/5 found that action learning in the healthcare sector is growing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(p. 21). Bell et al (2007) suggested that action learning promotes individual ownership of learning and development. Brook (2010), in a national survey within the NHS in 2004/5 found that action learning in the healthcare sector is growing.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Action-learning encourages reflection on actions and learning from each other. Used with a group of different professionals it can address organisational change [ 25 ] and has been used in a range of settings including mental health [ 26 ], managers on leadership programmes [ 27 ] and care homes [ 28 ].…”
Section: Introductionmentioning
confidence: 99%